KEEFEKTIFAN MODEL PEMBELAJARAN PROBLEM BASED INTRODUCTION (PBI) DALAM PEMBELAJARAN KETERAMPILAN MENULIS NASKAH DRAMA SISWA KELAS XISMA NEGERI 8 YOGYAKARTA - Mashuri, Riyadi, Wisni Nugrahaningtyas, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research is aimed at revealing 1) the differences in the skills of play writingbetween the group taught play writing by using the Problem Based Introduction (PBI) teachingmodel and the group taught play writing without using the model; 2) the effectiveness ofProblem Based Teaching (PBI) teaching model in teaching play writing to the grade XI studentsof SMAN 8 Yogyakarta.The method used in this research is quasi-experiment controlled group design. Thereare two variables in this research. They are Problem Based Teaching (PBI) teaching model asthe independent variable and the students’ play writing skill as the dependent variable.The results of the research show that there is a significant difference between theplay writing skill of the students who are taught by using Problem Based Teaching (PBI)teaching model and of those who are taught without using the model. The teaching of playwriting skill to the year XI students of SMAN 8 Yogyakarta by using this model proves to bemore effective.